2014
DOI: 10.5194/bgd-11-17925-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glacial meltwater and primary production as drivers for strong CO<sub>2</sub> uptake in fjord and coastal waters adjacent to the Greenland Ice Sheet

Abstract: Abstract. The Greenland Ice Sheet releases large amounts of freshwater, which strongly influences the physical and chemical properties of the adjacent fjord systems and continental shelves. Glacial meltwater input is predicted to increase strongly in the future, but the impact of meltwater on the carbonate dynamics of these productive coastal systems remains largely unquantified. Here we present seasonal observations of the carbonate system in the surface waters of a west Greenland tidewater outlet glacier fjo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…For a given photoperiod, the rate of CO 2 depletion also increased with increasing CO 2 supply (Fig. 3B), from 200 ppm, characteristic of contemporary Arctic conditions during spring and summer ( 25 , 27 , 28 ) and exceeding the minimum levels observed in situ within the Arctic kelp canopy (Fig. 1), to 400 and 1000 ppm, reflecting a CO 2 -enriched situation possibly met in the future.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…For a given photoperiod, the rate of CO 2 depletion also increased with increasing CO 2 supply (Fig. 3B), from 200 ppm, characteristic of contemporary Arctic conditions during spring and summer ( 25 , 27 , 28 ) and exceeding the minimum levels observed in situ within the Arctic kelp canopy (Fig. 1), to 400 and 1000 ppm, reflecting a CO 2 -enriched situation possibly met in the future.…”
Section: Resultsmentioning
confidence: 80%
“…40 m ( 37 ) interspaced with communities of benthic microalgae and with scarce occurrence of eelgrass meadows at 1 to 3 m depth ( 38 ) and rich intertidal communities ( 21 ). More details on Kobbefjord are available ( 26 , 28 ), including data acquired in parallel to those reported here in neighboring kelp sites ( 21 ). Fortuna Bay is a shallow (ca.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies (Sejr et al, 2011;Rysgaard et al, 2012and Meire et al, 2014 have shown that the fjords and shelf areas of Greenland have an exceptional high potential for CO2 uptake. Measurements of pCO2 were carried out in July-August from 2006-2009 in the High Arctic fjord, Young Sound by Sejr et al, (2011).…”
Section: Pco2 In Fjord and Coastal Surface Watermentioning
confidence: 99%
“…Another possible pump mechanism driving uptake of CO2 in the costal sea around Greenland is the inflow of melt water from land and the Greenland ice sheet. Because of the nonconservative behaviour of CO2 in water, the mixing of meltwater and sea water will result in strongly under saturated surface water with respect to CO2 (Meire et al, 2014).…”
Section: Introductionmentioning
confidence: 99%